2022
DOI: 10.1021/acs.jctc.1c01055
|View full text |Cite
|
Sign up to set email alerts
|

GLOW: A Workflow Integrating Gaussian-Accelerated Molecular Dynamics and Deep Learning for Free Energy Profiling

Abstract: We introduce a Gaussian-accelerated molecular dynamics (GaMD), deep learning (DL), and free energy profiling workflow (GLOW) to predict molecular determinants and map free energy landscapes of biomolecules. All-atom GaMD-enhanced sampling simulations are first performed on biomolecules of interest. Structural contact maps are then calculated from GaMD simulation frames and transformed into images for building DL models using a convolutional neural network. Important structural contacts are further determined f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 97 publications
4
65
0
Order By: Relevance
“…Recently, we have integrated the GaMD, Deep Learning and free energy prOfiling Workflow (GLOW) to predict important reaction coordinates and map free energy profiles of biomolecules (Do et al, 2022). First, GaMD simulations are performed on the target biomolecules (Fig.…”
Section: Machine Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have integrated the GaMD, Deep Learning and free energy prOfiling Workflow (GLOW) to predict important reaction coordinates and map free energy profiles of biomolecules (Do et al, 2022). First, GaMD simulations are performed on the target biomolecules (Fig.…”
Section: Machine Learningmentioning
confidence: 99%
“…Finally, the free energy profiles of these reaction coordinates are calculated through reweighting of GaMD simulations to characterize the biomolecular systems of interest (Fig. 4D) (Do et al, 2022). GLOW was successfully demonstrated on characterization of activation and allosteric modulation of a GPCR, using the adenosine A1 receptor (A1AR) as a model system.…”
Section: Machine Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] Computational and mutagenesis studies have reported interesting insights about the A 1 R activation and allosteric modulation identifying important residues for the signaling efficacy of agonists and cooperativity of PAMs. [18, 22, 23] Despite all these achievements, a detailed characterization of the allosteric networks that drive receptor activation and G-proteins binding is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, "selective GaMD" algorithms, including Ligand GaMD (LiGaMD) 22 , Peptide GaMD (Pep-GaMD) 23 , and Protein-Protein Interaction-GaMD (PPI-GaMD) 24 have been developed to enable repetitive binding and dissociation of small-molecule ligands, highly exible peptides, and proteins within microsecond simulations, which allow for highly e cient and accurate calculations of ligand/peptide/protein binding free energy and kinetic rate constants 19 . Recently, GaMD has been combined with deep learning and free energy pro ling into GLOW to predict molecular determinants and map free energy landscapes of biomolecules 25 .…”
Section: Introductionmentioning
confidence: 99%